Implementation : how to transform strategic initiatives into blockbuster results - Brache, Alan P., 1950- (McGraw Hill Companies, 2005)
Implementation delivers the tactics and tools you need to effectively put your corporate goals and strategies into practice, fuel organisational growth, and ensure your company's long-term success. It provides a clear road map, structure, and the practical tools for every business or organisation to ensure it accomplishes its most critical projects.